Descriptive analysis of the profile of gram-negative bacteria in a university hospital (Research, Society and Development, 2023)
Objective: To evaluate both the profile of gram-negative bacteria and of  hospitalized patients at the Hospital Universitário Regional dos Campos Gerais, from January to July 2022. Methods: This is an observational study with a cross-sectional, retrospective design, carried out at Hospital Universitário Regional dos Campos Gerais. 344 electronic medical records of all patients who had positive identification for gram-negative bacteria in bacterial culture tests were analyzed using the Philips Clinical Informatics platform. Results: Regarding the epidemiological profile, it was shown that patients over 65 years of age are the most affected by gram-negative bacteria, with men being the main ones identified with positive culture samples. As for the microbiological profile, the urine culture was responsible for 46.5% of the positive cultures. Among all gram-negative bacteria identified, klebsiella pneumoniae was the most prevalent microorganism among them, found in 48% of the samples. Regarding the profile of resistance to penicillins, they were resistant in 82.3% of all positive samples for gram-negative bacteria. Conclusions: It was possible to identify that multidrug-resistant bacteria are a significant problem for the analyzed hospital, since the consequences presented by patients affected by these microorganisms were worrying, with a high average length of stay and a high rate of deaths.